Running against Windmills: Costly Perseverance in Long- and Short-Term Goal Pursuit - Anna L. M. Daelen (ZBW - Leibniz Information Centre for Economics, 2025)
This paper provides evidence of costly perseverance in the field. In a setting where consultants select and pursue projects autonomously, I show that perseverance is related with fewer successfully completed projects as well as lower sales and commissions. Using rich firm data on individual job activity, I shed light on the task-specific behavioral mechanisms. Overall, perseverant consultants start fewer projects. In fast markets, the lower number of projects started is the main channel of costly perseverance; in slower markets, costs primarily arise from pursuing projects in a more isolated and uninformed way, as shown by an inefficient allocation of effort between stakeholders. The survey questions driving costly perseverance point to the consultants' failure to incorporate negative signals and opportunity costs into their effort allocation. Using heterogeneity within and between consultants' task assignment, I show that perseverance is more costly in exploration tasks as opposed to well-defined tasks characterized by mere exploitation.
Keywords: M51; J24; J63; 330; grit; job performance; productivity; tenacity; motivation